Identification of Promising Lead Compounds from Capsicum annuum Targeting BACE-1 for Alzheimer’s Disease Therapy: A Molecular Docking Study - Aisiri Vijayasimha; Samiksha Bhor (International Journal of Genetic Modifications and Recombinations, 2023)
Background: Alzheimer's disease (AD) is a neurodegenerative disorder affecting millions of people worldwide. Beta-secretase 1 (BACE-1) is an important therapeutic target for AD treatment. Capsicum annuum (CA) is a commonly consumed plant with potential neuroprotective properties. In this study, we aimed to identify potential lead compounds from CA that can target BACE-1 for AD therapy using molecular docking. Methods: A library of 15 compounds from CA was obtained from PubChem, and their structures were optimized using PyRx-v0.8. BACE-1 protein structure was obtained from the Protein Data Bank (PDB). Docking simulations were performed using PyRx-v0.8, and the results were analyzed using BIOVIA Discovery Studio 2019. Results: Among the studied 15 ligands, the best binding affinity was shown by 6 compounds. Capsaicin, Dihydrocapsaicin, Apigenin, Riboflavin, Quercetin, and Luteolin had a binding affinity of -6.4, -8.4, -8.4, -8.5, and -8.7 kcal/mol respectively. Luteolin had the highest binding score of -8.7 kcal/mol, this indicates its best possible inhibitory action with BACE-1. Conclusion: Our study identified Dihydrocapsaicin, and Capsaicin from CA as promising lead compounds that can target BACE-1 for AD therapy. Further in vitro and in vivo studies are needed to validate their therapeutic potential.
Keywords: Alzheimer’s disease; BACE-1; Capsicum annuum; molecular docking